Three-dimensional shape analysis of coarse aggregates: New techniques for and preliminary results on several different coarse aggregates and reference rocks - Quiroga, Pedro Nel; fowler, david; Erdogan, Sinan; Saleh, H.A.; Livingston, Richard; Garboczi, Edward J.; Ketcham, Peter M.; Hagedorn, John G.; Satterfield, Steven G. (ElSevier, 2006)
The shape of aggregates used in concrete is an important parameter that helps determine many concrete properties, especially the rheology of fresh concrete and early-age mechanical properties. This paper discusses the sample preparation and image analysis techniques necessary for obtaining an aggregate particle image in 3-D, using X-ray computed tomography, which is then suitable for spherical harmonic analysis. The shapes of three reference rocks are analyzed for uncertainty determination via direct comparison to the geometry of their reconstructed images. A Virtual Reality Modeling Language technique is demonstrated that can give quick and accurate 3-D views of aggregates. Shape data on several different kinds of coarse aggregates are compared and used to illustrate potential mathematical shape analyses made possible by the spherical harmonic information

La forma de los áridos utilizados en el hormigón es un parámetro importante que ayuda a determinar muchas propiedades del hormigón, especialmente la reología del hormigón fresco y las propiedades mecánicas a edades tempranas. En este artículo se analizan las técnicas de preparación de muestras y análisis de imágenes necesarias para obtener una imagen tridimensional de las partículas de los áridos mediante tomografía computarizada de rayos X, que resulta adecuada para el análisis armónico esférico. Se analizan las formas de tres rocas de referencia para determinar la incertidumbre mediante comparación directa con la geometría de sus imágenes reconstruidas. Se demuestra una técnica de lenguaje de modelado de realidad virtual que puede proporcionar vistas tridimensionales rápidas y precisas de agregados. Se comparan los datos de forma de varios tipos diferentes de agregados gruesos y se utilizan para ilustrar los posibles análisis matemáticos de forma que posibilita la información armónica esférica.
Keywords: Image and shape analysis; Aggregate; Composite; Modeling